2006
DOI: 10.1007/s10741-006-0232-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in the evaluation of non-ischemic cardiomyopathies: Current applications and future perspectives

Abstract: Patients with non-ischemic cardiomyopathy often represent a diagnostic challenge, and correct etiologic diagnosis may influence outcomes. Lately, delayed myocardial enhancement MR imaging has been developed and is currently being used for a growing number of clinical applications. On delayed enhancement MR images, scarring or fibrosis appears as an area of high signal intensity, and the pattern by which this enhancement occurs in the myocardium allows distinction of many different pathologies. In nonischemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 114 publications
(120 reference statements)
0
18
0
1
Order By: Relevance
“…In nonischemic dilated cardiomyopathy (DCM), fibrosis tends to be patchy, subepicardial, or midmyocardial in distribution (13)(14)(15). It has been shown that non-CRT patients with DCM and midwall fibrosis have a higher risk of mortality and unplanned hospitalizations, as well as a higher risk of sudden cardiac death (16).…”
Section: Discussionmentioning
confidence: 99%
“…In nonischemic dilated cardiomyopathy (DCM), fibrosis tends to be patchy, subepicardial, or midmyocardial in distribution (13)(14)(15). It has been shown that non-CRT patients with DCM and midwall fibrosis have a higher risk of mortality and unplanned hospitalizations, as well as a higher risk of sudden cardiac death (16).…”
Section: Discussionmentioning
confidence: 99%
“…It appears, therefore, that the extent of myocardial tissue injury, rather than the mere deterioration of cardiac contractile function, is a crucial risk factor in NIHD patients. To date, systematic data on the extent and distribution pattern of LHE in patients with NIHD are scarce although a number of excellent review articles addressed the topic [9][10][11][12]. The methodological evaluation of these parameters would likely be valuable for longitudinal studies and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it allows for the precise determination of left ventricular ejection fraction (LVEF). 8 To date, a number of studies evaluating the clinical occurrence of AICM have been reported using 2-dimensional (2D) echocardiographic indices in the setting of breast cancer, 9,10 acute myeloid leukemia, 11 and lymphomas. [12][13][14] However, recent studies conducted in adults have shown that conventional 2D echocardiographic indices may not accurately predict the onset of heart failure in patients with AICM.…”
mentioning
confidence: 99%